Association between preconditioning absolute lymphocyte count and transplant outcomes in patients undergoing matched unrelated donor allogeneic hematopoietic stem cell transplantation with reduced-intensity conditioning and anti-thymocyte globulin. (December 2021) - Seo, Jeongmin; Shin, Dong-Yeop; Koh, Youngil; Kim, Inho; Yoon, Sung-Soo; Min Byun, Ja; Hong, Junshik
Background: Allogeneic stem cell transplantation (alloSCT) offers cure chance for various hematologic malignancies, but graft- versus -host disease (GVHD) remains a major impediment. Anti-thymocyte globulin (ATG) is used for prophylactic T-cell depletion and GVHD prevention, but there are no clear guidelines for the optimal dosing of ATG. It is suspected that for patients with low absolute lymphocyte counts (ALCs), current weight-based dosing of ATG can be excessive, which can result in profound T-cell depletion and poor transplant outcome. Methods: The objective of the study is to evaluate the association of low preconditioning ALC with outcomes in patients undergoing matched unrelated donor (MUD) alloSCT with reduced-intensity conditioning (RIC) and ATG. We conducted a single-center retrospective longitudinal cohort study of acute leukemia and myelodysplastic syndrome patients over 18 years old undergoing alloSCT. In total, 64 patients were included and dichotomized into lower ALC and higher ALC groups with the cutoff of 500/μl on D-7. Results: Patients with preconditioning ALC <500/μl were associated with shorter overall survival (OS) and higher infectious mortality. The incidence of acute GVHD and moderate-severe chronic GVHD as well as relapse rates did not differ according to preconditioning ALC. In multivariate analyses, low preconditioning ALC was recognized as an independent adverse prognostic factor for OS. Conclusion: Patients with lower ALC are exposed to excessive dose of ATG, leading to profound T-cell depletion that results in higher infectious mortality and shorter OS. Our results call for the implementation of more creative dosing regimens for patients with low preconditioning ALC.